2014
DOI: 10.5740/jaoacint.12-198
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trace Amounts of Ethylene Glycol and its Analogs in Water Matrixes by Liquid Chromatography/Tandem Mass Spectrometry

Abstract: Contamination of drinking water by ethylene glycol (EG) is a public health concern. EG causes adverse health effects in humans and animals, including cardiopulmonary and acute renal failure. EG and other glycols, such as propylene glycol (PG) are major components in antifreeze liquids, which may be the main source of contamination of ground water. A sensitive LC/electrospray ionization (ESI)-MS/MS method was developed to measure trace amounts of EG, diethylene glycol, and 1,2- and 1,3-PG in several water sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Thus we established protocols to measure both by HPLC with a combination of UV and MS detection. EG detection is potentiated by derivatization using benzoyl chloride (Schotten–Baumann reaction) and extracted with pentane. , Two mass transitions were used to detect and quantify EG, and the quantification limit (LoQ) for the assay was 2.5 pg (corresponding to 0.5 ng mL –1 , Figure A). UV detection was also achievable at 237 nm, but the sensitivity was three orders of magnitude lower, and an unidentified coeluting peak hindered accurate quantification.…”
Section: Resultsmentioning
confidence: 99%
“…Thus we established protocols to measure both by HPLC with a combination of UV and MS detection. EG detection is potentiated by derivatization using benzoyl chloride (Schotten–Baumann reaction) and extracted with pentane. , Two mass transitions were used to detect and quantify EG, and the quantification limit (LoQ) for the assay was 2.5 pg (corresponding to 0.5 ng mL –1 , Figure A). UV detection was also achievable at 237 nm, but the sensitivity was three orders of magnitude lower, and an unidentified coeluting peak hindered accurate quantification.…”
Section: Resultsmentioning
confidence: 99%
“…The main direction of fragmentation of molecular ions was the sequential loss of diethylphosphoryl groups with the formation of ions [М-CH 3 It was found that the interaction of glycols with DEP at 60°C for 45 min was the optimum (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Glycols are usually determined as derivatives, which improves their chromatographic properties. Glycols are converted into benzyl ethers [2,3] and determined by using HPLC. In the gas-chromatographic (GC) determination, glycols are converted into methyl [4] and trimethylsilyl ethers [5], and into complex ethers of butyl-or phenylboronic acids [6,7].…”
mentioning
confidence: 99%
“…Benzoyl chloride (BC) can derivatize (benzoylate) amines (primary and secondary) and alcohol groups into amides and esters, respectively, via a base-catalyzed Schotten–Baumann reaction (Figure S1). BC-based derivatization has been applied widely in biochemical and environmental settings. BC reacts quickly in aqueous and organic solution at room temperature and is available in isotopically labeled forms, enabling the use of paired SIL-IS. Benzoyl derivatives are stable in cold storage and in the light and can be detected with ultrahigh performance liquid chromatography (UV–HPLC), LCMS, and GC-MS. For molecules with multiple derivatizable functional groups, BC methods can produce single- or multilabeled derivatives by modification of derivatization or extraction procedures.…”
Section: Introductionmentioning
confidence: 99%